Growth performance and survival of guppy (Poecilia reticulata): different formulated diets effect - Anka, Ishrat Zahan; Jothi, Jakia Sultana; Sarker, Joyshri; Talukder, Avijit; Islam, Md Sadrul (Asian Journal of Medical and Biological Research, 2016)
Growth performance of guppy fries was assessed by providing four different types of formulated diets comprised of some available ingredients (fish meal (FM), prawn meal (PM), meat and bone meal (MBM), wheat flour (WF), corn flour (CF), starch (S) and soya bean oil) and the result was compared with supplied commercial diet as control. After 30 days experimental period, diet 1 (FM: PM=6:1) showed the best result in case of length gain (0.48 cm) in guppies whereas lowest (0.01 cm) was reported from diet 2 (PM: MBM= 4:3). The body weight gain in guppies was also found higher (0.004 g) in diet 1 than other diets. Specific growth rate (SGR) of all formulated diets was between 1.03% to 4.8% while 0.7% was found in commercial diet. Maximum survival rate (95%) was recorded in formulated diet 1 whereas 80% was investigated in control .Growth trend of guppies from all the supplied formulated diets resulted better rather than the imported commercial diets. So, Commercial diets might be replaced by experimental diets for the better production of guppy. Asian J. Med. Biol. Res. September 2016, 2(3): 451-457